Negative aggregate accounting earnings and gross domestic product: A perspective of conditional accounting conservatism at the macroeconomic level - Atmini, Sari; Prastiwi, Arum (University of Islam Malang, 2024)
This study explores the role of corporate accounting earnings in predicting GDP growth at a macroeconomic level. It investigates whether negative aggregate accounting earnings are more effective predictors of GDP growth than positive earnings and how macroeconomic uncertainty affects this predictive ability. The two main novelties introduced in this study are the integration of two distinct streams of research, namely, the usefulness of accounting earnings and conditional accounting conservatism at the macroeconomic level and the consideration of the moderating role of macroeconomic uncertainty. Data from 22 countries from 2008 to 2022 are analyzed using moderated regression analysis. The findings support the theory that negative earnings are better predictors of GDP than positive earnings, aligning with the conditional accounting conservatism perspective. Furthermore, this study also reveals that macroeconomic uncertainty specifically weakens the predictive strength of negative aggregate accounting earnings and aggregate operating income on GDP growth. This comprehensive insight underscores the critical importance of considering economic conditions when employing accounting earnings to forecast economic trends, emphasizing that negative earnings are particularly significant indicators during uncertain economic times.